PENGUJIAN MODEL TERINTEGRASI VARIABEL ANTECEDENTS DAN OUTCOMES PADA PERCEIVED ORGANIZATIONAL SUPPORT (POS) - Jati Waskito (Benefit: Jurnal Manajemen dan Bisnis, 2004)
This study was conducted at society health central throughout DIY to develop and testing a model of the antecedent and consequences of POS, based on social exchange theory. All thevariables adapted from expert in organizational study, all items were reliable and valid. Structuralequation analyses indicate that POS have unique antecedents and are differentially related tooutcome variables